Evolution of nano-pores during annealing of technically pure molybdenum sheet produced from different sintered formats. (January 2023) - Jakob, S.; Lorich, A.; Knabl, W.; Stark, A.; Staron, P.; Clemens, H.; Spoerk-Erdely, P.; Maier-Kiener, V.
Abstract: Molybdenum is a refractory metal with no phase transformation in the solid state and a high melting point. It is therefore an excellent structural material for various high temperature applications. Especially in this field of operation, significant creep resistance is essential. To achieve this, a microstructure with grains in the range of millimeters is desired. However, as demonstrated in the present study, the onset temperature for secondary recrystallization, which would lead to a beneficial grain size, is among other things dependent on the initial dimensions of the sintered part. One possible reason for the different microstructural evolutions is the influence of residual pores in sub-micrometer size. Sheets were thus fabricated via three different production routes employing the same initial Mo powder to exclude chemical variation as an influencing factor. The samples were investigated by in-situ small-angle X-ray scattering at a synchrotron radiation source with two different heating rates. Additionally, selected annealed samples were studied ex-situ with high energy X-rays. The apparent volume fraction of pores is compared to a volatilization model for the vaporization of typical accompanying elements and the induced thermal expansion. Graphical abstract: Unlabelled Image Highlights: Mo sheet shows different secondary recrystallization behavior for different dimensions of the initial sintered part. The volume fraction of sub-micrometer pores increases with temperature. The volatilization of accompanying elements is suggested as a reason for additional pores at higher temperatures. Pores can inhibit the migration of grain boundaries and therefore impede secondary recrystallization.